A methodology to determine maintenance criticality using AHP. (30th July 2008) - Sachdeva, Anish; Kumar, Dinesh; Kumar, Pradeep
The aim of this paper is to develop a new maintenance decision strategy by integrating the criticality of various factors related to failure and repair of a component/subsystem as an alternative to traditional approach of Failure Mode and Effect Analysis (FMEA). The methodology presented is based on Analytical Hierarchical Process (AHP) technique which will provide an aid to the maintenance managers/analysts to formulate an efficient and effective priority ranking of the various components/failure modes based on a number of maintenance issues. The principles of the theory and an actual case from a paper industry is undertaken to illustrate the use of the proposed methodology.